2012
DOI: 10.1620/tjem.227.297
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adipose Tissue Volume Estimated at Imaging Sites 5-6 cm Above L4-L5 Is Optimal for Predicting Cardiovascular Risk Factors in Obese Japanese Men

Abstract: The association between visceral adipose tissue (VAT) with cardiovascular disease (CVD) has been clearly demonstrated. Although typical VAT area at 4th and 5th lumbar vertebrae (L4-L5) is used to approximate VAT volume, growing evidence has suggested that this measurement site may not be ideal. However, these findings for Asian people remain unclear. Thus, we searched for the better VAT measurement sites associated with CVD risk factors in obese, Japanese men. Eighty-two obese men were included in a cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
(37 reference statements)
1
10
0
1
Order By: Relevance
“…For this study, we chose the single-slice image located 5 cm above L4-L5 to compare to the single-slice image at the level of L4-L5, which is the traditional site of origin, because our previous studies showed the þ 5 cm site to be most closely associated with VAT volume. 10,11 Furthermore, results from our previous studies for the areas 6 and 5 cm above L4-L5 were almost identical (data not shown).…”
Section: Magnetic Resonance Imagingsupporting
confidence: 51%
See 1 more Smart Citation
“…For this study, we chose the single-slice image located 5 cm above L4-L5 to compare to the single-slice image at the level of L4-L5, which is the traditional site of origin, because our previous studies showed the þ 5 cm site to be most closely associated with VAT volume. 10,11 Furthermore, results from our previous studies for the areas 6 and 5 cm above L4-L5 were almost identical (data not shown).…”
Section: Magnetic Resonance Imagingsupporting
confidence: 51%
“…Furthermore, our ongoing research evaluates the relationship between single-slice imaging and total VAT and subcutaneous adipose tissue (SAT) volume. 10,11 We concluded that the area 5-6 cm above L4-L5 is a better predictor of VAT volume than the cross-sectional L4-L5 image, and it changes with diet and exercise. This is similar to the results of previous studies.…”
Section: Introductionmentioning
confidence: 88%
“…97 It is not clear, however, exactly which sagittal slice best correlates with total VAT volume and CVD risk factors. Commonly, a sagittal slice obtained at the L4-L5 level is used to approximate VAT volume 98 ; however, Shen et al 99 studied an ethnically and racially diverse group of people and found that different abdominal levels are more predictive of VAT volume than the L4-L5 level. Among men, a single slice at 10 cm above L4-L5 was most predictive of VAT volume; among women, 5 cm above L4-L5 was most predictive.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Ис-следования ВЖТ на данном уровне показывают максимальную воспроизводимость и высокую точ-ность измерений. В ряде работ [29,30] показано, что оценка ВЖТ на 5-6 см выше L4-L5 является более точной при проведении МРТ и КТ в динамике.…”
Section: компьютерная томография (кт) и магнитно-резонансная томографunclassified